2019
DOI: 10.4314/njbas.v26i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and impact of improved groundnut seed varieties among groundnut farmers: Case of Albasu Local Government Area of Kano State, Nigeria

Abstract: This study assessed the level of adoption and impact of improved groundnut seed varieties among groundnut farmers in Albasu Local Government Area of Kano State, Nigeria. A multistage simple random sampling was used to select the respondents across the local government area, wards and villages to give 120 respondents. Data were collected with structured questionnaire and analyzed with simple descriptive statistics, Z-test and logit regression analysis. Results showed that for both adopters and non-adopters, maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, the yield of the crop stood at 800kg/ha, far below the obtainable yield of 3000kg/ha . This concurred with previous empirical research in adoption of groundnut practices conducted in Kano state Northwestern Nigeria reported farmers' yield of 800-1100kg/ha (Shuaibu, 2018). Low yields obtained has hindered both the domestic and global supply requirements by 90% (Thawur et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…However, the yield of the crop stood at 800kg/ha, far below the obtainable yield of 3000kg/ha . This concurred with previous empirical research in adoption of groundnut practices conducted in Kano state Northwestern Nigeria reported farmers' yield of 800-1100kg/ha (Shuaibu, 2018). Low yields obtained has hindered both the domestic and global supply requirements by 90% (Thawur et al, 2021).…”
Section: Introductionsupporting
confidence: 87%
“…In the second level, purposive sampling was used for the collection of groundnut farmers from each of the four countries involved in the project. The questionnaire design was focused on previous related research (Ndjeunga et al, 2013;Shuaibu et al, 2018) and was divided into four parts. The first segment covered the sociodemographic details and characteristics of growers, consisting of age group, family size and wages, cooperative participation, educational status, planted varieties of groundnuts and the total size of cultivated land.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…The uptake and effect analysis of new groundnut varieties reported an uptake rate of 31 per cent in Nigeria (Ndjeunga et al, 2013). Groundnut pod yields from farmland in Kano, Nigeria remained small at an estimate of 1082 kg/ha relative to an on-site yield of 3000 kg/ha (Shuaibu, 2018). Likewise, a survey conducted by Rekwot et al (2015) in Nigeria found that the yield of farmers (800 kg/ha) was far below the expected on-site production of 3000 kg/ha.…”
Section: Introductionmentioning
confidence: 99%
“…Kano State represents the Sahel Savannah regionand is made up of about 20,760 square Km2, with 86,000 hectares of dry-season irrigation farmland, 75,000 hectares of fallow and grazing land and 1,754,200 hectares of ordinary farm land (Kano ADP, 2011). The State has 400-1,200mm average rainfall per annum and temperature range of 14.02 0 C-32.03 0 C. The citizens are mostly farmers, traders and partisans and own about 4 hectares of farmland per person on the average (Shuaibu, 2018).Nasarawa Staterepresents the Guinea Savannah regionand is a cosmopolitan State, which lies in the central part of Nigeria within Longitude 7 0 0'E-9 0 37'E and Latitude 7 0 45'N-9 0 25'N. It covers about 27,137.8Km 2 and is populated with about 2,523,400 people (NBS, 2016).…”
Section: Study Areamentioning
confidence: 99%